PENGARUH RETURN ON ASSETS (ROA) TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN GOOD CORPORATE GOVERNANCE (GCG) SEBAGAI VARIABEL MODERASI (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2014-2018) - Ardila Hi Wahid; Muhsin N Bailusy (Jurnal Manajemen Sinergi, 2020)
Objective: This research aims to know and analyze the influenceof Return On Asset(ROA) to the company’s value with thedisclosure of Corporate Social Responsibility (CSR) and GoodCorporate Governance (GCG) as moderation variables (casestudies on Manufakturing Companies listed on the indonesia StockExchange (IDX) Period (2014-2018). Samples in this study usedthe purposive sampling method. Based on the selection ofsamples according to the criteria specified, the number of samplesin this study was as much as 20 companies or as many as 100observation units in a 5 year period.Methodology: The analytical methods used in this study were twonamely multiple regression analyses and moderated regressionanalysis.Finding: H1 and H2, are accepted, but H3 no accepted at the 5%confidence level.Conclusion: The results showed that Return On Asset (ROA)positively impacted the value of the company. The greater thevalue of ROA, showing the better performance of the company,because the rate of return on investment is greater. However, CSRas a moderation variable is not able to moderate the influence ofReturn On Asset (ROA), The value of the company. The low of thepilot is because the shareholders or stakeholders focus more onthe company's performance or focus solely on the amount of profitgenerated. GCG as a moderation variable is unable to moderatethe influence of Return On Asset (ROA) on the company's valueDue to the percentage of shares ownership by managers are stillvery small constraints in optimizing the GCG mechanism within thecompany.